Cost of achieving HbA1c and weight loss treatment targets with IDegLira vs insulin glargine U100 plus insulin aspart in the USA - Billings LK; Mocarski M; Basse A; Hunt B; Valentine WJ; Jodar E (Dove Medical Press, 2019)
LK Billings,1,2 M Mocarski,3 A Basse,4 B Hunt,5 WJ Valentine,5 E Jodar6 1Division of Endocrinology and Metabolism, NorthShore University HealthSystem, Skokie, IL, USA; 2Department of Medicine, University of Chicago Pritzker School of Medicine, Chicago, IL, USA; 3Value Evidence and Outcomes, Novo Nordisk Inc., Plainsboro, NJ, USA; 4Market Access- Region AAMEO, Novo Nordisk Pharma Gulf FZ-LLC, Dubai, United Arab Emirates; 5Health Economics, Ossian Health Economics and Communications, Basel, Switzerland; 6Department of Endocrinology and Clinical Nutrition, H.U. Quirón Salud Madrid & Ruber Juan Bravo, Universidad Europea de Madrid, Madrid, Spain Background: Compared with basal-bolus insulin therapy (insulin glargine U100 plus insulin aspart), IDegLira has been shown to be associated with similar improvements in HbA1c, with superior weight loss and reduced hypoglycemia in patients with type 2 diabetes. The present analysis evaluated the cost per patient with type 2 diabetes achieving HbA1c-focused and composite treatment targets with IDegLira and insulin glargine U100 plus insulin aspart (≤4 times daily). Methods: The proportions of patients achieving treatment targets were obtained from the treat-to-target, non-inferiority DUAL VII study (NCT02420262). The annual cost per patient achieving target (cost of control) was analyzed from a US healthcare payer perspective. The annual cost of control was assessed for eight prespecified endpoints and four post-hoc endpoints. Results: The number needed to treat to bring one patient to targets of HbA1c <7.0% and HbA1c ≤6.5% was similar with IDegLira and insulin glargine U100 plus insulin aspart. However, when weight gain and/or hypoglycemia were included, the number needed to treat was lower with IDegLira. IDegLira and insulin glargine U100 plus insulin aspart had similar costs of control for HbA1c <7.0%. However, cost of control values were substantially lower with IDegLira when the more stringent target of HbA1c ≤6.5% was used, and when patient-centered outcomes of hypoglycemia risk and impact on weight were included. Conclusion: IDegLira was shown to be a cost-effective treatment vs insulin glargine U100 plus insulin aspart for patients with type 2 diabetes not achieving glycemic targets on basal insulin in the USA. Keywords: basal-bolus insulin, cost-effectiveness, diabetes mellitus, GLP-1 receptor agonist, IDegLira, USA